The epistemic bases of prejudice: The role of need for cognitive closure - Baldner, Conrad (2019)
Social psychologists have long studied the factors that underlie prejudice, including rigid ways of viewing the world and a fear of outside influence. More recent research has focused on the need for cognitive closure, or the desire for epistemic certainty, and how this can lead to prejudice. Individuals who desire secure knowledge can turn to stereotypes that provide it; individuals under a need for cogni-tive closure can be more likely to accept these stereotypes and the resulting prejudicial attitudes. How-ever, the need for cognitive closure can, paradoxically, be used to reduce prejudice, by substituting a prejudiced source of knowledge with a positive source. In the following review, we will trace the de-velopment of these ideas, build connections between literatures, and propose a new future direction.